What we know about gender and rural climate services: Preliminary findings and guidance - Huyer, Sophia; Hansen, James; Rose, Alison; Vaughan, Catherine; Huysen, Tiff van (2017)
This brief summarizes preliminary findings and recommendations from an ongoing review of literature and CCAFS experience on gender-related challenges in empowering smallholder farming communities through climate services.